2014
DOI: 10.7182/pit2014111
|View full text |Cite
|
Sign up to set email alerts
|

Successful Kidney Transplant from Methanol-Intoxicated Donors

Abstract: The well-described disparity between the need for and the supply of organs suitable for transplant is growing. Because of this disparity, mortality of patients listed for transplant is increasing. Donors who die of intoxication (including victims of methanol poisoning) represent less than 1% of suitable donors and might be used to increase the supply of organs. They are often not accepted as donors by transplant specialists, because of concerns about patients' outcomes with these grafts. Three cases of fatal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In our review of the literature from the past 20 years, we found that 49 kidneys, 1 heart, 1 liver, 1 lung, and 2 corneal transplants were performed. Most of them indicated favorable long-term graft function and recipient survival ( Table 1 ) (7) , (8) , (9) , (10) , (11) , (12) , (13) , (14) , (15) . Although available data including the follow-up period are limited, it is most likely that the survival of organ grafts procured from donors who died due to methanol does not differ in the short- and long-term from transplants performed with organs from donors who died from other causes (16) .…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature from the past 20 years, we found that 49 kidneys, 1 heart, 1 liver, 1 lung, and 2 corneal transplants were performed. Most of them indicated favorable long-term graft function and recipient survival ( Table 1 ) (7) , (8) , (9) , (10) , (11) , (12) , (13) , (14) , (15) . Although available data including the follow-up period are limited, it is most likely that the survival of organ grafts procured from donors who died due to methanol does not differ in the short- and long-term from transplants performed with organs from donors who died from other causes (16) .…”
Section: Discussionmentioning
confidence: 99%